Universality of aging: family caregivers for elderly cancer patients - Baider, Lea; Surbone, Antonella (Frontiers in Psychology, 2014)
The world population is ageing, with the proportion of older people (65+ years) expected to reach 21% in 2050 and to exceed the number of younger people (aged 15 or less) for the first time in history. Because cancer is particularly a chronic disease of older people, a large increase in the number of elderly patients with cancer is anticipated. The estimated number of new cancer cases worldwide among people over 65 is expected to grow from about 6 million in 2008 to more than 11 million during the coming decade. By 2030, individuals over 65 are expected to account for 70% of all cancer patients in the Western world. Along with the increase in oncology patients, the number of older people caring for their ill spouses or other relatives is also growing, with the ensuing toll on these caregivers causing major concern, especially in western countries. In different societies the characteristics of family caregiver stressors, cultural norms concerning care giving, and the availability of support have a huge impact on those providing care. Any study of older caregivers of older cancer patients requires an integrative evaluation of ageing that takes into account cultural, social, psychological, and behavioral variables. This review proposes a critical discussion of the multidimensionality of the caregiving and of the impact that age, culture and gender have on it.